An experimental investigation of a high radius pre-swirl cooling system - Peng,Z; New,P; Long,CA; Childs,PRN (2007)
An experimental investigation into pre-swirl effectiveness and receiver hole discharge coefficient characteristics for a high radiusinjection pre-swirl cooling systems was carried out on an engine representative experimental rig with a 450 mm diameter rotor. Thereceiver holes and pre-swirl nozzles were located at a radius of 181 mm and 180 mm respectively. The experimental work was conductedat 5000-12000 rpm, 4 bar absolute pressure and 1.132 kg/s air supply. The maximum air supply temperature was 190ºC. Pressureand temperature distributions in the pre-swirl system were examined with an emphasis on the velocity effectiveness of thepre-swirl system as a whole and on the discharge coefficients of the rotating 'receiver holes' in the rotor. The results showed that thevelocity effectiveness increased with increasing swirl ratio resulting in reduced blade cooling flow temperature. Increasing the sealflow rate reduced the effectiveness. For the coefficient of discharge, it increased with increase in swirl ratio for most speeds. Thecoefficient of discharge also decreased with an increase in inner seal flow rate.